Effect of pharmacist interventions on pulmonary function parameters of Iraqi asthmatic patients: A comparative study - Marwan S. Ibrahim,; Mohammed, Mohammed Mahmood (Iraqi Journal of Pharmaceutical Sciences, 2023)
Background: Despite the fact that asthma is a long-term disease that may be treated, many people are unable to control their symptoms due to a lack of knowledge about their condition. The study's purpose was to find out if a pharmacist intervention improved asthma management because of this.Objective: this study designed to assess the effect of pharmaceutical care on pulmonary functions test.Method: The study was completed in three months. The patients who were enrolled were divided into two groups: Group 1 consists of 23 asthma patients who were randomly assigned to receive conventional therapy for chronic bronchial asthma based on disease stage and severity, as well as a pharmaceutical care plan that includes patient care and education, for three months. Group 2: Included in the study were 21 asthma patients who were randomly randomized to receive only conventional therapy for chronic bronchial asthma based on illness stage and severity for three months. All individuals included in this trial had their ACT and PFT levels checked at the start and three months later.Result: the conclusion of the study, patients who received a verbal and written pharmaceutical implementation plan significantly improved their asthma control by increasing medication adherence, which was accompanied by an improvement in mean ACT and PFT scores for the interventional group when compared to the control group after 3 months of follow up.Conclusion: The results of the study approved the important role of the pharmacist in asthma control to improve medication adherence and enhancing PFT and this mean increase asthma control